Aktivitas Fisik dan Pola Makan dengan Kadar Gula Darah pada Pasien Diabetes Melitus (Window of Nursing Journal, 2026)
Diabetes Mellitus is a disease that occurs due to excessive blood sugar levels (hyperglycemia) in response to the inability of the pancreas to produce insulin. This study aims to determine the relationship between physical activity and diet with blood sugar levels in diabetes mellitus patients at UPT Puskesmas Tana Lili. The research design used was an analytic descriptive design with a cross sectional approach using a total sampling technique with a sample of 43 respondents. The relationship test was carried out using the chi square test with a significance level of α